Analisis Faktor-Faktor Yang Mempengaruhi Pengungkapan Tanggung Jawab Sosial Pada Perusahaan Di Bursa Efek Indonesia - Supriyanto, Supriyanto; Putra, Rio (Global Financial Accounting Journal, 2017)
This study aims to measure the factors that affect social responsibility in companies listed on the Indonesia Stock Exchange (IDX). The variables used in the study are social responsibility of the company as the dependent variable while profitability, leverage, firm size, and the size of Public Accountant as independent variables